Pre-Hospital Cath Lab Activation: The Role Of Emts In Enhancing Heart Attack Outcomes (The Review of Diabetic Studies, 2025)
Timely reperfusion is the cornerstone of survival and improved prognosis in acute myocardial infarction, particularly ST-elevation myocardial infarction (STEMI). Emergency Medical Technicians (EMTs) have emerged as key players in bridging the gap between symptom onset and definitive hospital-based care. Pre-hospital activation of the cardiac catheterization laboratory (cath lab) by EMTs based on pre-hospital electrocardiograms (ECGs) and clinical assessments has been shown to reduce door-to-balloon times, minimize myocardial damage, and improve survival outcomes. This review explores the evidence supporting EMT-driven early activation of the cath lab, examines the systems and protocols that facilitate this process, and highlights the technological and organizational advancements enabling streamlined pre-hospital decision-making. Ethical, legal, and logistical considerations are also discussed, along with barriers to implementation in different healthcare systems. By synthesizing global data, the article emphasizes the critical role of EMTs in modern cardiac care and provides a roadmap for optimizing pre-hospital STEMI management to ensure better patient outcomes.